2013
DOI: 10.1142/s0129065713500202
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Feature Selection and Classification Approaches to Enhance Information From Overnight Oximetry in the Context of Apnea Diagnosis

Abstract: This study is aimed at assessing the usefulness of different feature selection and classification methodologies in the context of sleep apnea hypopnea syndrome (SAHS) detection. Feature extraction, selection and classification stages were applied to analyze blood oxygen saturation (SaO2) recordings in order to simplify polysomnography (PSG), the gold standard diagnostic methodology for SAHS. Statistical, spectral and nonlinear measures were computed to compose the initial feature set. Principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 54 publications
1
63
0
22
Order By: Relevance
“…21,41 Notwithstanding, previous studies demonstrated that our approach could be easily optimized for any technical setting in order to achieve a high diagnostic performance. 24,42 In addition, current high-performance oximeters already match technical characteristics of in-hospital equipment overcoming previous limitations of portable devices due to restrictions in memory storage capability and battery life. Finally, the proposed methodology presented herein aims to confirm or discard the presence of OSA (ie, to perform binary classification).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,41 Notwithstanding, previous studies demonstrated that our approach could be easily optimized for any technical setting in order to achieve a high diagnostic performance. 24,42 In addition, current high-performance oximeters already match technical characteristics of in-hospital equipment overcoming previous limitations of portable devices due to restrictions in memory storage capability and battery life. Finally, the proposed methodology presented herein aims to confirm or discard the presence of OSA (ie, to perform binary classification).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Therefore, an individual or chromosome from the population is just a combination of features (ie, a feature subset from the initial oximetric feature space composed of 18 features). A two-symbol binary codification was used to encode each feature subset or individual in the population, where the k-th bit denotes the absence (0) or the presence (1) of the k-th feature.…”
Section: Feature Selection and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, MsE has shown its usefulness to study heart rate dynamics [22], to find differences in the HRV from healthy subjects and subjects suffering from congestive heart failure and atrial fibrillation [23], to show different behaviours in the heart rate of young and elder [23], to quantify the complexity of human gait [24], to improve the knowledge of the EEG behaviour in AD patients [25], as well as to evaluate the effects of drugs in the EEG of schizophrenia patients [26]. Moreover, spectral entropy (SE) has been helpful to quantify the depth of anaesthesia in EEG recordings from women undergoing gynaecological surgery [27], to detect endpoints in speech signals recorded in noisy environments [28], to show the changes that AD causes in the spectrum of magnetoencephalographic and EEG recordings [17,29], as well as to enhance the automatic detection of SAHS from single-channel SpO2 recordings obtained during nocturnal oximetry [30].…”
mentioning
confidence: 99%